MR-Spectroscopy and Survival in Mice with High Grade Glioma Undergoing Unrestricted Ketogenic Diet. (31st December 2021) - Ciusani, Emilio; Vasco, Chiara; Rizzo, Ambra; Girgenti, Vita; Padelli, Francesco; Pellegatta, Serena; Fariselli, Laura; Bruzzone, Maria Grazia; Salmaggi, Andrea
Abstract: Glioblastoma multiforme (GBM) is considered the most malignant form of primary brain tumor. Despite multimodal treatment, prognosis remains poor. Ketogenic diet (KD) has been suggested for the treatment of GBM. In this study, the syngenic, orthotopic GL261 mouse glioma model was used to evaluate the effects of KD on the metabolic responses of the tumor using 7T magnetic resonance imaging/spectroscopy. GL261 cells were injected into the caudate nucleus of mice. Following implantation, animals were fed with standard chow or underwent a KD. 18 days after initiating the diet, mice fed with KD displayed significantly higher plasmatic levels of ketone bodies and survived longer than those fed with the standard diet. Decreased concentrations of gamma-aminobutyric acid, N-Acetyl-Aspartate and N-acetylaspartylglutamate were found in tumor tissue after 9 days into the KD, while a huge increase in beta-hydroxybutyrate (bHB) was detected in tumor tissue as compared to normal brain. The accumulation of bHB in the tumor tissue in mice undergoing the KD, may suggest either elevated uptake/release of bHB by tumor cells, or the inability of tumor cells in this context to use it for mitochondrial metabolism.